The art of Roger Winter : fire and ice - Kalil, Susie, 1952- (Sara and John Lindsey series in the arts and humanities, 2020)
Roger Winter has always been preoccupied with "recording reality in all its strangeness," in the words of biographer and art historian Susie Kalil. His works partake of wide-ranging influences: childhood memories of gospel hymns blaring from a loudspeaker atop the "Holy Roller" church near his home; strange totems composed of crows, foxes, angels, and old family photographs; rusted cars resting among chest-high weeds; faces reflected in the windows of a New York City bus. According to his siblings, he has been an artist since he was "pre-verbal," and in a career spanning eight decades, he has continually reinvented himself, breaching the boundaries of one stylistic convention after another?never content to allow the expression of his vision to be constrained to a single vocabulary.In this definitive retrospective of Winter?s life and art, Kalil explores not only the myriad influences of the artist and his dizzying stylistic journey but also allows Winter?s work to pose important questions: Why do some people become artists and others don?t? What gives artists their unique modes of perception and expression? Where is the line of separation between what is seen and what is represented? Between the maker and what is made??The Art of Roger Winter: Fire and Ice offers an in-depth portrait of one of today?s most important American painters. Critics, collectors, scholars, students, and art lovers will glean deep insights from this study in contrasts.